Analisis Kehilangan Energi Pada Pipa PVC Akibat Belokan Dan Perubahan Penampang - Ramdan, Ramdan; Yusuf, Andi Rumpang; Cangara, Satriawati (Program Studi Teknik Sipil Universitas Bosowa, 2024)
Water is a very important need for life on earth, especially living things such as humans, plants, animals and others. To meet these water needs, humans make various efforts to get it. Energy loss is a factor that affects the capacity of pipes as a means of conducting the flow of both water and oil. Energy loss leads to a reduction in flow discharge. Energy loss is caused by several factors including the roughness of pipe walls. In general, in a pipeline installation, two types of energy loss are known, namely energy loss due to friction and energy loss due to changes in miners and other accessories. From the test results, the largest energy loss occurred in the 3/4 pipe (P1 and P2) inch of 0.0092 m, also having a large flow speed of 0.579 m / second. The cause of the large energy loss due to friction between fluid and pipe walls or called major losses (hf) in normal pipes is greater than pipe cross-sectional changes and pipe bend resistance. Meanwhile, the flow speed in a normal pipe with a diameter of 2 inches has a flow speed of 0.080 m / s and an energy loss of 0.0000657 m and a flow speed in a normal pipe with a diameter of 3/4 inch has a flow speed of 0.571 m / s and an energy loss of 0.0033 m.